(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
This article is devoted to the analysis of Alexander Feinberg’s poem "Chig’ir". The article scientifically studies the content, philosophical motives and artistic features of the poem. Feinberg symbolically expresses human labor, the continuous movement of time and harmony with nature in the image of a chig’ir. The article also analyzes Rustam Musurmon’s translation of the poem from Russian into Uzbek. The translation is of great importance in preserving the philosophical content and artistic tone of the poem and bringing Feinberg’s work to Uzbek readers. The article highlights the significance of the poem in Uzbek literature and its contribution to the development of modern philosophical lyrics. Keywords Alexander Feinberg, Chig’ir, Rustam Musurmon, philosophical lyrics, translation, Russian literature, Uzbek literature, artistic analysis, nature and man.